Evidence construction of Silibinin capsules against alcoholic liver disease based on a meta-analysis and systematic review - Wang, Yan; Yang, Wenmin; Yang, Yuan; Liu, Xingning; Peng, Lanfen; Huang, Qi; Fan, Kongli; Hu, Rui; Yi, Jinyu; Zhong, Xin; Li, Jing; Sun, Jialing; et al. (Frontiers in Pharmacology, 2025)
BackgroundIn recent years, the incidence of alcoholic liver disease (ALD) has rapidly increased worldwide, becoming a significant health issue. Silibinin capsules have shown potential in treating ALD, but clinical evidence is still insufficient. This meta-analysis aimed to evaluate the efficacy and safety of Silibinin capsules in the treatment of ALD.MethodsThe study was registered with PROSPERO (CRD42024509676). Randomized controlled trials (RCTs) were included from six databases, covering the period from database inception to 30 December 2023. Primary outcomes included liver function indicators such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), total bilirubin (TBIL), lipid indicators including triglycerides (TG) and total cholesterol (TC), coagulation indicators including prothrombin time (PT), liver fibrosis indicator (PC-III), and Effective Rate. Analysis was performed using Review Manager 5.4.1 and STATA 14.0.ResultsIn 15 RCTs involving 1,221 patients, compared to the non-Silibinin group, Silibinin capsules showed significant efficacy in terms of liver function, lipid levels, and effective rate in patients with ALD. Detailed parameters were as follows: ALT [SMD = −1.16, 95% CI (−1.84, −0.47)], AST [SMD = −1.56, 95% CI (−2.18, −0.95)], GGT [SMD = −1.48, 95% CI (−2.09, −0.87)], TBIL [SMD = −1.14, 95% CI (−2.16, −0.13)], TG [SMD = −1.29, 95% CI (−1.93, −0.66)], TC [SMD = −1.11, 95% CI (−1.61, −0.61)], PT [SMD = −0.01, 95% CI (−0.29, 0.26)], PC-III [SMD = −1.94, 95% CI (−3.04, −0.84)], and Effective Rate [OR = 3.60, 95% CI (2.28, 5.70)]. Importantly, Silibinin capsules exhibited a favorable safety profile, with only mild gastrointestinal reactions and reports of insomnia as adverse events.ConclusionThis review reveals the clinical efficacy and safety of Silibinin capsules in the treatment of ALD, and confirms that the drug is an effective adjuvant therapy to alleviate ALD. At present, the mechanism of action of this drug for ALD is still unclear, and we expect more experimental studies to prove the clinical value of Silibinin capsules.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=509676.